Isometamidium chloride and homidium chloride fail to cure mice infected with Ethiopian Trypanosoma evansi type A and B - Mekonnen, Gebrekrustos; Mohammed, Elmi Fahiye; Kidane, Weldu; Nesibu, Awol; Yohannes, Hagos; Van Reet, Nick; Büscher, Philippe; Birhanu, Hadush (PLOS Neglected Tropical Diseases, 2018)
Background Trypanosoma evansi is mechanically transmitted by biting flies and affects camels, equines, and other domestic and wild animals in which it causes a disease called surra. At least two types of Trypanosoma evansi circulate in Ethiopia: type A, which is present in Africa, Latin America and Asia, and type B, which is prevalent in Eastern Africa. Currently, no information is available about the drug sensitivity of any Ethiopian T. evansi type. Methodology/principal findings This study was conducted with the objective of determining the in vivo drug sensitivity of two T. evansi type A and two type B stocks that were isolated from camels from the Tigray and Afar regions of Northern Ethiopia. We investigated the efficacy of four trypanocidal drugs to cure T. evansi infected mice: melarsamine hydrochloride (Cymelarsan), diminazene diaceturate (Veriben and Sequzene), isometamidium chloride (Veridium) and homidium chloride (Bovidium). Per experimental group, 6 mice were inoculated intraperitoneally with trypanosomes, treated at first peak parasitemia by daily drug injections for 4 consecutive days and followed-up for 60 days. Cymelarsan at 2 mg/kg and Veriben at 20 mg/kg cured all mice infected with any T. evansi stock, while Sequzene at 20 mg/kg caused relapses in all T. evansi stocks. In contrast, Veridium and Bovidium at 1 mg/kg failed to cure any T. evansi infection in mice. Conclusions/significance We conclude that mice infected with Ethiopian T. evansi can be cured with Cymelarsan and Veriben regardless of T. evansi type. In contrast, Veridium and Bovidium are not efficacious to cure any T. evansi type. Although innate resistance to phenanthridines was previously described for T. evansi type A, this report is the first study to show that this phenomenom also occurs in T. evansi type B infections.